The hidden globe: A case report on traumatic complete dislocation of the right globe into cranial cavity - Gan, Rick Kye; Abu Hasan, Muhammad Abdus-Syakur; Ibrahim, Maryam; Abdull Wahab, Shaik Farid; Fauzi, Mohd Hashairi; Yazid, Mohd Boniami; Ahmad, Mohammad Zikri (2020)
Objectives: To emphasise the role of point of care ultrasound (POCUS) as diagnostic modality in investigation of orbital trauma and to share an extremely rare case of eyeball dislocation into anterior cranial fossa. Case Report: A 65-year-old gentleman presented to the hospital after a lorry’s container accidentally fell over his face with complaints of right sided facial pain with loss of right eye vision and missing the right eyeball. Patient was fully conscious, orientated and hemodynamically stable. There was absent of right eye from its orbit and mechanical ptosis of the upper eyelid with intact right facial nerve. Other neurological examinations were normal. Results: Our POCUS showed that the distance between the right eyelid and right eyeball was significantly increased, there was loss of continuity of the orbital roof indicating fracture and dislocation of the bone fragments and the eyeball can be seen using the ultrasound to be dislocated superiorly and posteriorly into the anterior cranial fossa with intact right eye globe. All findings correlate with computed tomography brain scan report. Discussion: Eyeball dislocation into anterior cranial fossa is an extremely rare presentation and this is the 3rd case reported so far. Ultrasound has been proven to be demonstrated satisfactory sensitivity (92%) and specificity (100%) and positive predictive value (100%) in diagnosing orbital fractures when compared to CT scan. Conclusion: Ultrasound users should aware of the ability of ultrasound to diagnose not just orbital wall fracture but also eyeball dislocation and determined its direction of herniation.